High Prevalence of Multidrug-resistant Organisms: MRSA, VRE, CRE, ESBLs, and C. difficile at a Chicago LTACH. (4th October 2017) - Barza, Ruby; Wyant, Kodi; Patel, Parul; Patel, Jignesh; Mendoza, Katherine; Mangold, Kathy; Chavez, Natali; Kim, Kihe; Hines, David; Singh, Kamaljit
Abstract: Background: Multidrug-resistant organisms (MDROs) have been described in Chicago with long-term acute care hospitals (LTACHs) considered as the sites of amplification of these organisms. Accurate identification of colonized patients is an important strategy for decreasing the spread of MDROs. Methods: We conducted a point-prevalence study of Carbapenem-resistant Enterobacteriaceae (CRE), Extended spectrum B-lactamases (ESBL), Vancomycin-resistant Enterococci (VRE), Methicillin-resistant Staphylococcus aureus (MRSA) and Clostridium difficile (Cdif) carriage among patients in a Chicago LTACH in April 2017. Rectal specimens were collected using 1 double-headed rayon swab (Copan) and 1 FecalSwab (Copan). Anterior nasal swabs were collected using a separate swab. ESBL and CRE cultures were performed using CHROMagar ESBL media (Hardy). ESBL phenotypic confirmation was done using double-disc synergy method per CLSI guidelines. In addition, direct CRE PCR was performed using the Xpert ® Carba-R assay and an in-house PCR for blaKPC/NDM. VRE and MRSA culture was done using CNA agar (BD) and ChromMRSA agar (BBL). Bacterial identification and susceptibility was performed using MALDI-TOF and disc diffusion. Cdif PCR was performed using Xpert C. difficile/Epi assay. Results: A total of 81 patients were eligible for the study; 6 declined. Data were analyzed for 75 patients. Mean age of patients was 59 years (range: 24-90) and 45/75 (60%) patients were male. Fifty-four of 75 (72%) patients had at least 1 MDRO. Eighteen of 75 (24%) patients had CRE rectal colonization; 17 blaKPC PCR positive and 1 positive for blaKPC/NDM/VIM . The CREs in 16/18 (89%) patients were K. pneumoniae ; 1 E. cloacae, 1 M. morganii and 1 with both K. pneumoniae and E . A erogenes . Overall, 11/18 (61%) of CRE positive patients were also co-colonized with another MDRO. Seventeen of 75 (23%) patients had ESBLs, 13 /75 (17%) had MRSA, 31/75 (41%) had VRE and 6/75 (8%) had Cdif colonization. Conclusion: We found a high rate of MDRO colonization among patients in this Chicago LTACH. Comprehensive MDRO surveillance among LTACH patients is required to limit spread of significant pathogens. Disclosures: All authors: No reported disclosures.